2019
DOI: 10.1096/fj.201900234r
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitochondrial metabolism in murine skeletal muscle by the medium‐chain fatty acid receptor Gpr84

Abstract: Fatty acid receptors have been recognized as important players in glycaemic control. This study is the first to describe a role for the medium‐chain fatty acid (MCFA) receptor G‐protein‐coupled receptor (Gpr) 84 in skeletal muscle mitochondrial function and insulin secretion. We are able to show that Gpr84 is highly expressed in skeletal muscle and adipose tissue. Mice with global deletion of Gpr84 [Gpr84 knockout (KO)] exhibit a mild impairment in glucose tolerance when fed a MCFA‐enriched diet. Studies in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 79 publications
(114 reference statements)
0
39
1
Order By: Relevance
“…Gpr84 upregulation in the brain, bone marrow, and kidney in NOD mice, and in the aortae of ApoE -/high-fat diet mice suggests an involvement in inflammation associated with diabetes and atherosclerosis. Mice fed a MCFAenriched high-fat diet for 8 weeks did not reveal a significant increase of GPR84 in quadriceps muscle, but mice on methionine-and choline-deficient diets and choline-deficient, l-amino acid-defined, high-fat diets showed higher GPR84 expression in the liver (Montgomery et al, 2019;Puengel et al, 2020). These studies imply GPR84 has a role in inflammatory processes underlying various chronic noncommunicable conditions such as diabetes, atherosclerosis, and nonalcoholic fatty liver disease, and that long-term GPR84 expression might be relevant under pathological conditions.…”
Section: Mcfa-gpr84 Kinetic Disconnectmentioning
confidence: 85%
See 3 more Smart Citations
“…Gpr84 upregulation in the brain, bone marrow, and kidney in NOD mice, and in the aortae of ApoE -/high-fat diet mice suggests an involvement in inflammation associated with diabetes and atherosclerosis. Mice fed a MCFAenriched high-fat diet for 8 weeks did not reveal a significant increase of GPR84 in quadriceps muscle, but mice on methionine-and choline-deficient diets and choline-deficient, l-amino acid-defined, high-fat diets showed higher GPR84 expression in the liver (Montgomery et al, 2019;Puengel et al, 2020). These studies imply GPR84 has a role in inflammatory processes underlying various chronic noncommunicable conditions such as diabetes, atherosclerosis, and nonalcoholic fatty liver disease, and that long-term GPR84 expression might be relevant under pathological conditions.…”
Section: Mcfa-gpr84 Kinetic Disconnectmentioning
confidence: 85%
“…Gpr84 was undetected in a direct analysis of the four chambers of hearts in mice (Moore-Morris et al, 2009). In skeletal muscle, Montgomery et al (2019) highlight that Gpr84 transcripts are present across more mouse tissue types, including skeletal muscle, when considered relative to total RNA rather than normalized to Gapdh. Despite repeated doubts about GPR84 antibody specificity (Recio et al, 2018), Western blots indicated receptor protein was present in skeletal muscle and adipose tissue, and at low levels in the heart (Montgomery et al, 2019).…”
Section: Heart and Skeletal Muscle Expressionmentioning
confidence: 89%
See 2 more Smart Citations
“…Many lipid metabolism-related genes were in cluster 2 in both inoculum cohorts. This includes: PLA2G4A, which encodes a phospholipase involved in membrane lipid remodeling and biosynthesis of lipid mediators of the in ammatory response (32,33); GPR84, which serves as a receptor for free fatty acid (34); CD5L, which encodes a regulator of lipid synthesis that in turn regulates in ammatory response mechanisms and T cell activities (35); and ALOX15, which encodes a lipoxygenase that catalyzes the deoxygenation of polyunsaturated fatty acids and has known roles in red cell maturation and the in ammatory immune response (36). Several lipid metabolism-related genes that were in cluster 2 in the low inoculum cohort were in cluster 3 in the high, indicating that they continued to increase expression levels throughout infection and recovery.…”
Section: Metabolismmentioning
confidence: 99%